Adsorption of methylene blue from aqueous solution on pyrolyzed petrified sediment - Aroguz, Ayse Z.; Gulen, J.; Evers, R. H. (ELSEVIER SCI LTD, 2008)
The adsorption kinetics of methylene blue on pyrolyzed petrified sediment (PPS) has been performed using a batch-adsorption technique. The effects of various experimental parameters, such as initial dye concentration, contact time, and temperature were investigated. The pseudo-first-order and pseudo-second-order kinetic models were used to describe the kinetic data. The best correlation coefficient was obtained using the pseudo first-order kinetic model, which shows that the adsorption of methylene blue followed the pseudo-first-order rate expression and the rate constants were evaluated. The Langmuir and Freundlich adsorption isotherm models were applied to describe the equilibrium isotherms and the isotherm constants were determined. It was found that the data fitted well to Langmuir and Freundlich models. The activation energy of adsorption was also evaluated for the adsorption of methylene blue onto pyrolyzed sediment. It was found about 8.5 kJ mol(-1). Thermodynamics parameters Delta G degrees, Delta H degrees, Delta S degrees were calculated, indicating that this process can be spontaneous and endothermic. The adsorption enthalpy and entropy were found as 14-18.5 kJ mol(-1) and 52.8-67 J mol(-1) K-1, respectively. The results obtained from the adsorption process using PPS as adsorbent was subjected to student's t-test. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: methylene blue; adsorption kinetic; adsorption isotherm; sediment; pyrolysis; WASTE-WATER; BASIC DYE; ACID DYES; REMOVAL; KINETICS; AZINPHOSMETHYL; BENTONITE; CU(II); OCEAN; EARTH; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels